(untitled) (Ustozlar uchun, 2026)
This study examines the four primary functional categories of English sentences: declarative, interrogative, imperative, and exclamatory. By analyzing their syntactic arrangements and communicative purposes, the research demonstrates how word order and punctuation signal intent. The study concludes that mastery of these structures is essential for grammatical precision and effective interpersonal communication.